2015
DOI: 10.1063/1.4922867
|View full text |Cite
|
Sign up to set email alerts
|

Site occupancy and magnetic properties of Al-substituted M-type strontium hexaferrite

Abstract: We use first-principles total-energy calculations based on density functional theory to study the site occupancy and magnetic properties of Al-substituted M -type strontium hexaferrite SrFe12−xAlxO19 with x = 0.5 and x = 1.0. We find that the non-magnetic Al 3+ ions preferentially replace Fe 3+ ions at two of the majority spin sites, 2a and 12k, eliminating their positive contribution to the total magnetization causing the saturation magnetization Ms to be reduced as Al concentration x is increased. Our format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 40 publications
(81 reference statements)
4
23
0
Order By: Relevance
“…As shown in Fig. 1, 24 Fe 3+ ions of M-type hexaferrites are distributed in five different sublattices: 3 parallel sites (12 k , 2 a and 2 b ) and 2 antiparallel sites (4 f 1 and 4 f 2 )17. La-based substitutions could contribute to some Fe 3+ transforming into Fe 2+ at the 2 a and 4 f 2 sites18.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 1, 24 Fe 3+ ions of M-type hexaferrites are distributed in five different sublattices: 3 parallel sites (12 k , 2 a and 2 b ) and 2 antiparallel sites (4 f 1 and 4 f 2 )17. La-based substitutions could contribute to some Fe 3+ transforming into Fe 2+ at the 2 a and 4 f 2 sites18.…”
Section: Resultsmentioning
confidence: 99%
“…The result is that resultant magnetic moment and saturation magnetisation increases. For higher Al 3þ ion concentration (above x ¼ 0.6), Al 3þ ions enter 12K site [20]. 12K site has spin up electronic configuration.…”
Section: Resultsmentioning
confidence: 99%
“…From the magnetization curve the squareness ratio (M r /M s ) is less than 0.5. Such a material is good for recording medium [20]. For longitudinal magnetic recording medium high coercivity up to 600 Oe is required.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the magneto-crystalline anisotropy and coercive field of M-type strontium hexaferrite can be increased or reduced according to the concentrations of the substituted La 3+ cations. [20][21][22][23] Fe or Sr lattice sites are argued to be the strong preference for the La 3+ substitutions, which are thought to be responsible for the intrinsic physical mechanism of mag-netism modulation. Many efforts using the abovementioned techniques have been devoted to confirming the site preference of the substituted ions in M-type strontium hexaferrite.…”
Section: mentioning
confidence: 99%